Common reasoning in games: A Lewisian analysis of common knowledge of rationality - Robin P. Cubitt; Robert Sugden (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2011)
The game-theoretic assumption of common knowledge of rationality leads to paradoxes when rationality is represented in a Bayesian framework as cautious expected utility maximisation with independent beliefs (ICEU). We diagnose and resolve these paradoxes by presenting a new class of formal models of players' reasoning, inspired by David Lewis's account of common knowledge, in which the analogue of common knowledge is derivability in common reason. We show that such models can consistently incorporate any of a wide range of standards of decision-theoretic practical rationality. We investigate the implications arising when the standard of decision-theoretic rationality so assumed is ICEU.
Keywords: 330; common reasoning; common knowledge; common knowledge of rationality; David Lewis; Bayesian models of games